Capital Taxation in Japan and South Korea (1990s–2010s):Similar Outcomes, Different Trajectories. Issue 1 (1st January 2022) - Park, Sung Ho
ABSTRACT: This article examines the trajectories of capital tax policies in Japan and South Korea over recent decades. Historically, the two countries present an ideal case for studying fiscal developmentalism in East Asia. Total taxation was low, although capital owners assumed higher tax burdens than workers and consumers. From the 1990s to 2010s, both countries underwent a series of market-oriented tax reforms. A large body of political economy literature contends that the tax structures of these countries became increasingly neo-liberal during this period. Cuts in capital taxes were the primary focus of such changes. This article seeks to review this interpretation of the capital tax policies of Japan and South Korea. Through an examination of statutory and effective tax rate data, it confirms that no "race-to-the-bottom" cutbacks happened to capital taxation in these countries. Despite sharing this common ground, however, Japan's approach constitutes a more regressive case of capital tax adjustment than South Korea's. The author elucidates the reasons behind this difference by employing a revised partisan theory of capital taxation. The empirical analysis demonstrates the validity of this claim by examining eight cases of partisan governments in Japan and South Korea from the 1990s to the 2010s.